2007
DOI: 10.1136/bmj.39216.542442.be
|View full text |Cite
|
Sign up to set email alerts
|

Long term results of compression therapy alone versus compression plus surgery in chronic venous ulceration (ESCHAR): randomised controlled trial

Abstract: Objective To determine whether recurrence of leg ulcers may be prevented by surgical correction of superficial venous reflux in addition to compression.Design Randomised controlled trial.Setting Specialist nurse led leg ulcer clinics in three UK vascular centres.Participants 500 patients (500 legs) with open or recently healed leg ulcers and superficial venous reflux.Interventions Compression alone or compression plus saphenous surgery.Main outcome measures Primary outcomes were ulcer healing and ulcer recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
265
0
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 356 publications
(294 citation statements)
references
References 33 publications
8
265
0
21
Order By: Relevance
“…The ESCHAR trial21 found that 17 per cent of patients had died by 3 years, with no statistically significant difference between groups, or any mortality associated with surgery. This rate of mortality was greater than would be expected in the general population of the same age, reflecting the greater co‐morbidity associated with venous disease.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ESCHAR trial21 found that 17 per cent of patients had died by 3 years, with no statistically significant difference between groups, or any mortality associated with surgery. This rate of mortality was greater than would be expected in the general population of the same age, reflecting the greater co‐morbidity associated with venous disease.…”
Section: Methodsmentioning
confidence: 99%
“…The ESCHAR trial21 was a large, UK‐based, publicly funded RCT with a long follow‐up; these results are used to inform the natural history of venous leg ulcers with compression therapy (the comparator in the model). Fig .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations